HUBUNGAN POLA KONSUMSI KOPI DENGAN RESIKO KEJADIAN GASTRITIS PADA MASYARAKAT DI RT 10 RW 03 DESA MANCAR KECAMATAN PETERONGAN KABUPATEN JOMBANG - Olviana Serlince Bili; Prawito Prawito; Yusiana Vidhiastutik (Library Unit of the College of Health Science Husada Jombang, 2023)
Introduction: The caffeine content of coffee can accelerate the production of stomach acid, so that it becomes one of the risk factors for gastritis. This causes excess gas production in the stomach so that a person often complains of a feeling of bloating in the stomach with various complaints such as nausea and acid reflux. Objective: The purpose of this study was to determine the relationship between coffee consumption patterns and the risk of gastritis in RT 10 RW 03 Mancar Village, Peterongan Region, Jombang Regency. Methods: Cross-sectional analysis was used in the study design. The population in this study were people aged 20-55 years in RT 10 RW 03 Mancar Village with a total of 240 people. Purposive sampling was used as a sampling method for 60 respondents according to the inclusion criteria. The variables in this study were the independent variable coffee consumption patterns and the dependent variable the risk of gastritis. Data collection was carried out from the research results according to the questionnaire questions on December 18-24 2022 at the RT 10 RW 03 Mancar Village, Peterongan District. Jombang Regency. The analysis data used in this study was Spearmen Rho Test. Results: The results showed that almost half of the respondents were in the high category of coffee consumption, as many as 26 respondents (43.3%), and the incidence of gastritis showed that almost all respondents were at risk of gastritis, as many as 47 respondents (78.3%). With a 95% confidence level, the Spearman rank correlation statistical test gives results with a P value of (0.000) and a value of (0.05) indicating that these variables are related. The r value of 0.715 indicates a significant correlation. Conclusion: It can be concluded that the pattern of coffee consumption is associated with the risk of gastritis. And it is recommended that gastritis sufferers control their consumption patterns of coffee consumed every day, pay attention to the caffeine content in coffee. Because if caffeine is consumed beyond safe limits in the body it can cause an increase in stomach acid.